An Efficient Resource Management for Prioritized Users in Cloud Environment Using Cuckoo Search Algorithm. (2016) - Alexander, Aneena Ann; Joseph, Divya Lissia
Abstract: Cloud computing is a model which is empowered for on demand and convenient system access to a shared pool of computing resources. The clients of the cloud can be an individual or an association, and can acquire their respective services from cloud service provider. Advances in technologies, lead to the relocation from antiquated desktop devices to smart mobile devices. With a large increase in the number of mobile devices and bandwidth clients can execute as many tasks from their gadgets itself. Be that as it may, with versatility come its innate issues, for example, resource scarceness, finite energy and low network connectivity. This is, indeed, not only a temporary technological inadequacy but intrinsic to mobility and a hindrance that needs to be run over. Here in this paper, a load-aware allocation strategy is proposed and allocation is considered as an optimization problem with the aim of reducing the make span and the computational cost meeting the deadline constraints, with high resource utilization and is solved using Cuckoo-Search algorithm. The proposed approach is evaluated using Cloudsim framework and the results showed that our approach works better than other metaheuristic algorithms.